Deep Brain Stimulation of the Pedunculopontine Tegmental Nucleus (PPN) Influences Visual Contrast Sensitivity in Human Observers - Strumpf, Hendrik; Noesselt, Toemme; Schoenfeld, Mircea Ariel; Voges, Jürgen; Panther, Patricia; Kaufmann, Joern; Heinze, Hans-Jochen; Hopf, Jens-Max (PloS one, 2016)
The parapontine nucleus of the thalamus (PPN) is a neuromodulatory midbrain structure with widespread connectivity to cortical and subcortical motor structures, as well as the spinal cord. The PPN also projects to the thalamus, including visual relay nuclei like the LGN and the pulvinar. Moreover, there is intense connectivity with sensory structures of the tegmentum in particular with the superior colliculus (SC). Given the existence and abundance of projections to visual sensory structures, it is likely that activity in the PPN has some modulatory influence on visual sensory selection. Here we address this possibility by measuring the visual discrimination performance (luminance contrast thresholds) in a group of patients with Parkinson's Disease (PD) treated with deep-brain stimulation (DBS) of the PPN to control gait and postural motor deficits. In each patient we measured the luminance-contrast threshold of being able to discriminate an orientation-target (Gabor-grating) as a function of stimulation frequency (high 60Hz, low 8/10, no stimulation). Thresholds were determined using a standard staircase-protocol that is based on parameter estimation by sequential testing (PEST). We observed that under low frequency stimulation thresholds increased relative to no and high frequency stimulation in five out of six patients, suggesting that DBS of the PPN has a frequency-dependent impact on visual selection processes at a rather elementary perceptual level.